2021
DOI: 10.1017/nie.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

UK economic outlook: Brexit Britain in Covid recovery ward

Abstract: for helpful comments and Patricia Sanchez Juanino for preparing the charts and the database underlying the forecast. The forecast was completed on 25 January 2021, more recent data are incorporated in the text. Unless otherwise specified, the source of all data reported in tables and figures is the NiGEM database and NIESR forecast baseline. All questions and comments related to the forecast and its underlying assumptions should be addressed to Cyrille Lenoël

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Understanding the impacts of furlough is important because it was a key policy measure implemented to mitigate the economic disruption of the pandemic. Due to the UK CJRS furlough scheme, unemployment only rose moderately compared to other countries (Küçük et al, 2021), which is confirmed in our studies, as the number of furloughed workers was more than three times higher than the number of employees who lost their job. Unlike traditional forms of unemployment, the relationship between specific labour market policy interventions, such as furlough, and health is less well-understood (Korpi, 1997).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Understanding the impacts of furlough is important because it was a key policy measure implemented to mitigate the economic disruption of the pandemic. Due to the UK CJRS furlough scheme, unemployment only rose moderately compared to other countries (Küçük et al, 2021), which is confirmed in our studies, as the number of furloughed workers was more than three times higher than the number of employees who lost their job. Unlike traditional forms of unemployment, the relationship between specific labour market policy interventions, such as furlough, and health is less well-understood (Korpi, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Understanding the impacts of furlough is important because this policy was a key measure implemented to mitigate the economic disruption of the pandemic. Due to the UK CJRS furlough scheme, unemployment only rose moderately compared to other countries (Küçük et al, 2021). By December 2020, 9.9 million UK employees (about 36% of the employed workforce) had been furloughed (Hensher, 2020) and the number of people claiming unemployment-related benefits increased by 1.4 million.…”
Section: Discussionmentioning
confidence: 99%
“…Workers have experienced tremendous disruptions due to the pandemic [ 25 , 26 ], with many losing their job, being furloughed [ 27 ], experiencing changes in working hours [ 28 ], or shifting to working from home [ 29 , 30 ]. The impact of employment disruptions on mental and social wellbeing has been investigated [ 27 ], but little was known about the role of home working.…”
Section: Discussionmentioning
confidence: 99%
“…Workers have experienced tremendous disruptions due to the pandemic 18,19 , with many losing their job, being furloughed 20 , experiencing changes in working hours 21 , or shifting to working from home 22,23 . The impact of employment disruptions on mental and social wellbeing during the pandemic has been investigated 20 , but little is known about the role of home working.…”
Section: Discussionmentioning
confidence: 99%